Hubungan Pola Komsumsi, Penyakit Infeksi, Dan Pantang Makan Dengan Kejadian Kurang Energi Kronis (KEK) Pada Ibu Hamil Di Wilayah Kerja Puskesmas Napal Putih Bengkulu : The Relationship between Consumption Patterns, Infectious Diseases, and Abstinence from Eating with Chronic Energy Deficiency (CED) in Pregnant Women in Community Health Center Work Areas Bengkulu White Marl - Aryanti, Septia Linta; Tambunan, Novrida (Dohara POAJ, 2023)
Introduction: Nutritional problems are still a major public health problem in developing countries including Indonesia and are an indirect cause of maternal and child deaths, which are actually preventable. The condition of chronic energy deficiency (KEK) in pregnant women will occur if the body's needs are not fulfilled for a long time. Methods: This type of research uses a correlational quantitative analysis method using a retrospective approach to assess the independent variables Consumption patterns, and abstinence from eating during pregnancy, where this research is by interview and observation and data collection on independent and dependent variables collected simultaneously and during the time this research took place. The population of pregnant women who visited the UPT Puskesmas in June-July 2022 was 45 mothers. Sampling using total sampling. Data analysis was used using the Chi-square test. Results: The results of data analysis and processing found a relationship with the incidence of chronic energy deficiency (KEK) in pregnant women at UPT Puskesmas Napal Putih Bengkulu, namely Consumption Pattern p-value = 0,023; Infectious Diseases p-value = 0,041 and Abstinence from Eating p-value = 0,013. Discussion: The conclusion of this study is that there is a relationship between the variables patterns of consumption, infectious diseases, and abstained from eating with chronic energy leakage (ced) incidence in pregnant women in the work area of Napal White Health Center Bengkulu in 2022.